Keefektifan Penggunaan Desain Media Reproduksi Grafika dalam Pembelajaran Seni Rupa di SMP - Tjitjik Sri Wardhani (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2006)
The aim of this classroom action research is to improve the quality of fine arts subject and students' creativity through the use of graphical reproduction media design. The study involved 88 second graders of a junior high school and one fine-art teacher teaching those students. Data were collected through observation, field notes, documentation, interview, and recordings of program implementation. The results show that the use of graphical reproduction media design could enhance teaching learning quality and develop students' creativity, which in turn is expected to build up students' independence needed for their future life.